Pluractionality: A cross‐linguistic perspective. - Mattiola, Simone (Language & Linguistics Compass, 2020)
This paper aims to give a cross‐linguistic overview of pluractionality. Pluractionality is defined as a structural modification of the verb indicating the presence of multiple events. The paper first investigates the functions associated with pluractional markers in the languages of the world and classifies them into core and additional functions. I then present the most frequent marking strategies that the languages adopt in order to encode pluractionality and briefly discuss the morphological nature of one in particular (i.e., lexical alternation), as well as the formal identification of participant plurality. Finally, I examine the grammatical status of pluractionality in a cross‐linguistic perspective, taking the most recent typological literature into consideration. I conclude that "pluractionality" cannot be theoretically conceived as a unique, cross‐linguistically valid category but should rather be regarded as a label, which indicates different phenomena in different languages, useful for typological comparison but not reflecting any kind of pre‐established grammatical category.